Using sertraline in postpartum and breastfeeding: balancing risks and benefits. Issue 7 (3rd July 2018) - Cuomo, Alessandro; Maina, Giuseppe; Neal, Stephen M; De Montis, Graziella; Rosso, Gianluca; Scheggi, Simona; Beccarini Crescenzi, Bruno; Bolognesi, Simone; Goracci, Arianna; Coluccia, Anna; Ferretti, Fabio; Fagiolini, Andrea
ABSTRACT: Introduction: The World Health Organization recommends newborns to be breastfed but this may be challenging if the mother needs to be treated for depression, since strong evidence to inform treatment choice is missing. Areas covered: We provide a critical review of the literature to guide clinicians who are considering sertraline for the management of depression during postpartum. Expert opinion: Sertraline is one of the safest antidepressants during breastfeeding. In most cases, women already taking sertraline should be advised to breastfeed and continue the medication. We recommend to begin with low doses and to slowly increase the dose up, with careful monitoring of the newborn for adverse effects (irritability, poor feeding, or uneasy sleep, especially if the child was born premature or had low weight at birth). The target dose should be the lowest effective. When feasible, child exposure to the medication may be reduced by avoiding breastfeeding at the time when the antidepressant milk concentration is at its peak. A decision to switch to sertraline from ongoing and effective treatment should be taken only after a scrupulous evaluation of the potential risks and benefits of switching versus continuing the ongoing medication while monitoring the infant carefully.